2015
DOI: 10.1002/uog.14665
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of cervical length in women with twin pregnancy presenting with threatened preterm labor

Abstract: Objective To assess the accuracy and determine the optimal threshold of sonographic cervical length (CL) for the prediction of preterm delivery (PTD) (range, 0.653-0.724 vs 0.620-0.682, respectively; P = 0.3). The optimal threshold of CL for any given target sensitivity or specificity was lower in twin than in singleton pregnancies. However, in order to achieve a negative predictive value of 95%, a higher threshold (28-30 mm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The reason we comprehensively considered all the above factors when building the model was that the predictive performance of a single maternal factor or cervix geometry (including length) is not satisfactory, primarily due to poor sensitivity. [36][37][38][39][40] The mechanism of SPTB involves various mechanical stimuli (two continuously growing foetuses and the expanding uterus) and biochemical stimuli (in ammatory factors, fetoplacental signals and steroid hormones). 41,42 Compared to that in singleton pregnancies, the mechanism of SPTB in twin pregnancies is predominantly determined by overdistension, whereas the role of in ammation and microbiologic invasion of the amniotic cavity (MIAC) is relatively minor.…”
Section: Discussionmentioning
confidence: 99%
“…The reason we comprehensively considered all the above factors when building the model was that the predictive performance of a single maternal factor or cervix geometry (including length) is not satisfactory, primarily due to poor sensitivity. [36][37][38][39][40] The mechanism of SPTB involves various mechanical stimuli (two continuously growing foetuses and the expanding uterus) and biochemical stimuli (in ammatory factors, fetoplacental signals and steroid hormones). 41,42 Compared to that in singleton pregnancies, the mechanism of SPTB in twin pregnancies is predominantly determined by overdistension, whereas the role of in ammation and microbiologic invasion of the amniotic cavity (MIAC) is relatively minor.…”
Section: Discussionmentioning
confidence: 99%
“…Their results also showed that none of the women with CL ≥ 25 mm delivered within Table 4 Binary logistic regression analysis for prediction of preterm delivery within 7 days after first assessment and before 34 weeks' gestation, in twin pregnancies presenting with symptoms of threatened preterm labor 7 days after presentation. Melamed et al 6 evaluated the predictive accuracy of sonographic CL for preterm birth in 216 twin pregnancies with threatened preterm labor, focusing on the negative predictive value (NPV), and found that a NPV of 95% can be achieved with a CL cut-off of 28-30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies investigating assessment of twin pregnancy for risk of preterm birth have focused on asymptomatic patients. A large study comparing the value of CL measurement in symptomatic women with a twin ( n = 218) vs those with a singleton ( n = 1077) gestation, reported that, in order to achieve a negative predictive value of 95%, a threshold of 28–30 mm had to be used in twin pregnancy as compared to 11.5–12 mm in singletons. In a systematic review of the literature investigating CL measurements in twin pregnancies with threatened preterm labor, Liem et al .…”
Section: Introductionmentioning
confidence: 99%
“…Its isolated use as a screening tool has limited value due to low sensitivity. 16,25,26 In addition, previous research has demonstrated that the risk of PTB is also affected by maternal demographic features, such as ethnic origin, age, primiparity, chorionicity, prepregnancy body mass index (BMI) and history of previous preterm delivery or late-term abortion. [27][28][29][30][31][32] In a sense, twin gestation itself is one of the strongest risk factors for PTB.…”
Section: | Introductionmentioning
confidence: 99%